The Development of the Pedagogical Content Knowledge (PCK) Standard for Malaysian ICT Teachers - Sulaiman Sarkawi; Norhaziah Mohd Salleh; Mohamad Ibrahim; Amily Shafila Shariff; Noriza Nayan; Razana Baharudin (Pejabat Karang Mengarang UPSI, 2019)
The main aim of this study is to develop the Pedagogical Content Knowledge (PCK) standard for Malaysian ICT teachers. The researchers used the Delphi method to analyze data elicited from a group of practitioners, namely 245 expert ICT teachers who volunteered to participate in the study. Using this method, the teachers' opinions were elicited through three rounds of survey to reach a consensus regarding the importance of three domains of ICT teaching: (a) Knowledge of students and learning, (b) Knowledge of curriculum, and (c) Knowledge of teaching strategies. The analysis of the data showed that there were 13 important knowledge items required by ICT teachers, 45 very important knowledge items, and one moderate item. This finding helped the researchers in developing the PCK standard that can help institutions of higher learning to improve current training practices of ICT trainee teachers.